"Lembrando dos caminhos" : a escrita da memória em Fazendo Ana Paz, de Lygia Bojiunga - Silva, Edson Maria da (2017)
This study examines the writing of memory in Fazendo Ana Paz, by Lygia Bojunga considering it not as what must be reconstituted, but as what brings the past into the present in difference, creating a relation of both possibility and impossibility of reaching such a thing. As a method, we analyze in Fazendo Ana Paz the narrative focus, orality, writing, time, characters and narration. Our main theoretical endorsements are: Maurice Blanchot (2007), Lucia Castello Branco (1994), Jacques Derrida (2005), Gilles Deleuze (2002), Roland Barthes (2003) and the valuable support from philosophy such as: Friedrich Nietzsche (2007) and psychoanalysis, with Sigmund Freud (1996). Besides, literary texts of: Marcel Proust (2012), Clarice Lispector (1999), Maguerite Duras (1986) and Lewis Carroll (2009). We also have theoretical anchorage from the field of physics by Stephen Hawking (2015).